Overcoming Financial Barriers - Binsted, Anne; Paulley, Neil (European Journal of Transport and Infrastructure Research, 2009)
The funding process and the availability of both revenue and capital funding can create a barrier to the effective design, implementation and maintenance of sustainable transport and land-use schemes. The DISTILLATE Funding Project therefore sought to identify the nature of these barriers, how they are being experienced by local authorities, and the ways in which they could be overcome. This paper provides an overview of the findings of this project. The methodological approach included a series of consultations with transport practitioners and their counterparts in public health, environmental strategy, land-use planning and corporate policy units, three literature reviews, semi-structured telephone interviews with transport practitioners, two workshops and continual engagement with five case-study partners. The results of these research activities have been encapsulated within a Funding Toolkit, which has been designed to enable significant improvements in the way in which local authorities can manage, and overcome, funding barriers. Other research products include a guidance note for the funders of transport schemes, which provides stakeholders with an overview of the barriers faced by local authorities and recommendations about how they can be alleviated. This paper gives an overview of the research findings and details the role that both local authorities and the funders of transport and land use schemes can play in alleviating the impact of funding barriers.